Comparative Study of Antibacterial Activity of Tulsi, Garlic and Commercially used Antibiotics against Bovine Bacterial Endometritis using Molecular Docking Analysis - Arya, Damini; Tyagi, Rashmi; Sharma, Shingini; Sharma, Mridula (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted with the objective to find effective drug against bacterial bovine endometritis using Molecular docking. The antibacterial property of selected plants was studied and its comparison with conventional antibiotics was done. The plants selected for study were Tulsi and Garlic on the basis of its potent antibacterial activity. Selection of bacteria (S. aureus and E. coli) for the present study was done on the basis of most predominant bacteria causing bovine endometritis as observed in previous studies. The selected bacterial proteins were docked against phytochemicals of plants. Vital proteins of Staphylococcus aureus are Gyrase B (3G75), FtsA (3WQU), DNA ligase (3JSN), Dehydrosqualene synthase (3TFN) and Escherichia coli are FtsZ (6UMK), DNA gyrase (1KZN) and ZapD (5DKO). The docking procedure was carried out using Autodock. It was concluded that,  gentamicin (-6.95 Kcal/mol), enrofloxacin (-6.97 Kcal/mol) and Tulsi (-6.40 Kcal/mol) showed better binding affinity followed by garlic (-3.89 Kcal/mol).  Apigenin, one of the phytoconstituent of tulsi showed the better binding affinity among all the phytochemicals (ranging from -7.2 Kcal/mol to -9.2 Kcal/mol) of garlic and tulsi against targeted bacterial proteins, it can be taken into consideration alone after extraction or in combination therapy. Hence, Tulsi alone or in combination with garlic can be used for further in vivo or in vitro trials in a direction of effective drug discovery against bacterial bovine endometritis.
Keywords: molecular docking, endometritis, garlic, tulsi